2018
DOI: 10.1016/j.jamda.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Sodium Excretion and Cardiovascular Disease and Mortality in the Elderly: A Cohort Study

Abstract: Reduced sodium excretion is associated with increased mortality in a sample of community-dwelling older people, especially among the frail participants. High levels of sodium excretion are not associated with adverse outcomes in this population; therefore, sodium restriction might not be beneficial in older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 25 publications
1
40
0
Order By: Relevance
“…This systematic review identified only three out of nineteen studies that met the pre‐specified criteria for quality in a 6‐month period. Of these, a cohort study identified an association between lower sodium intake (<6.25 g/d) and increased mortality in Italian adults, most of whom consumed well above recommended sodium intakes assessed by single 24‐hour urine collections at baseline . Two randomized controlled trials confirmed the previously identified positive association between sodium intake and elevated blood pressure.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…This systematic review identified only three out of nineteen studies that met the pre‐specified criteria for quality in a 6‐month period. Of these, a cohort study identified an association between lower sodium intake (<6.25 g/d) and increased mortality in Italian adults, most of whom consumed well above recommended sodium intakes assessed by single 24‐hour urine collections at baseline . Two randomized controlled trials confirmed the previously identified positive association between sodium intake and elevated blood pressure.…”
Section: Discussionmentioning
confidence: 72%
“…The weekly search identified 4141 citations over the period from April 3 to October 30, 2018, of which 19 studies including dietary sodium and health outcomes met the criteria for full review (Table ). These included systematic review and meta‐analyses (n = 2), randomized controlled trials (n = 3, including one post hoc analysis of a randomized controlled trial), a non‐randomized controlled trial (n = 1), prospective cohort studies (n = 4), a retrospective cohort study using population data (n = 1), and cross‐sectional studies (n = 8) . Two studies assessed mortality outcomes, four studies assessed morbidity outcomes, and one study assessed symptoms/quality of life/functional status outcomes .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations